2022
DOI: 10.3390/microbiolres13020022
|View full text |Cite|
|
Sign up to set email alerts
|

An Assessment of the Lactic Acid-Producing Potential of Bacterial Strains Isolated from Food Waste

Abstract: Lactic acid (LA) is widely used in many industries as a crucial starting material in food products, bio-based materials, and biodegradable polymers. The goals of this research were to isolate LA bacteria from food wastes, assess their potential for LA production, and study their growth characteristics. In this study, six bacterial strains were isolated from food waste and identified using 16S rRNA gene sequencing; namely, Weissella viridescens WJ39, Leuconostoc lactis YS33, Leuconostoc citreum KD42, Leuconosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…As shown in Table 2, there were significant differences (p<0.05) in the kinetic parameters µx and Td obtained with the exponential model for the studied strains, namely L. citreum (20), L. mesenteroides (29) and W. viridescens (28), which showed the shortest doubling times and the highest specific growth rates (between 0.76 and 1.13 h-1). These data are similar to those presented by other authors [48], [49] for these same species. It should be noted that the growth kinetics parameters are influenced by the culture conditions and the composition of the medium and reveal the good metabolic adaptation of the strains to the substrate [50].…”
Section: Determination Of Growth Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Table 2, there were significant differences (p<0.05) in the kinetic parameters µx and Td obtained with the exponential model for the studied strains, namely L. citreum (20), L. mesenteroides (29) and W. viridescens (28), which showed the shortest doubling times and the highest specific growth rates (between 0.76 and 1.13 h-1). These data are similar to those presented by other authors [48], [49] for these same species. It should be noted that the growth kinetics parameters are influenced by the culture conditions and the composition of the medium and reveal the good metabolic adaptation of the strains to the substrate [50].…”
Section: Determination Of Growth Parameterssupporting
confidence: 93%
“…The values of µmax obtained in our study for these strains were similar when compared to other studies carried out with LAB in substrates such as Skim Milk and in selective culture media [30], [53]. Species of the genus Weissella have been highlighted in other investigations for presenting high growth rates, even higher than those of Leuconostoc [49]; which coincides with the behavior observed in the present study (Table 2).…”
Section: Determination Of Growth Parameterssupporting
confidence: 91%
“…As for the genus Bifidobacterium , of the phylum Actinobacteria , the diet that employed grape pomace in lambs [ 65 ], a food with high antioxidant power, presented an increase in its population, a result that agrees with other diets that have implemented antioxidants and that have presented an improvement in meat quality in terms of fatty acid content in lambs [ 172 ]. Bacteria of the genus Lactococcus , belonging to the order Lactobacillales , are considered within the group of lactic acid producing bacteria (LAB) [ 173 ]. Their presence was detected in Holstein Friesian cows in the diet presenting Ascophyllum nodosum [ 151 ].…”
Section: An Approach To the Functions Of Microorganismsmentioning
confidence: 99%
“…In a study conducted by Uwamahoro et al on the lactic acid production potential from bacterial strains originating from food waste, it was found that the Weissella viridescens WJ39 strain had the highest potential for lactic acid production. It's important to note that when utilizing waste, the efficiency of metabolite production is not the only concern; the fact that waste is being processed and converted into valuable compounds is crucial [113]. Moreover, further results also indicate the impact of LAB on the food industry and environment, namely, the produced lactic acid had an antimicrobial effect.…”
Section: Innovative Lab Fermentation Methods Supporting Sustainable F...mentioning
confidence: 97%